FACTORS AFFECTING TENDINOPATHOGENESIS. Issue 9 (10th May 2013) - Smith, M M; Ravi, V; Dart, A J; Sonnabend, D H; Little, C B
Abstract : Introduction: Tendon tears are common in both the ageing and sporting communities. Treatments that restore normal structure and function are lacking despite increasing knowledge of the inflammatory and matrix changes that occur in the tissue after a stress-induced injury. Increased cellularity, disruption of collagen fibre alignment and excessive accumulation of proteoglycans are a few of the temporal changes characterising this condition. Development of an animal model of surgically-induced tendinopathy in the sheep shoulder has enabled us to elucidate the progression of the condition over time and also to determine the effect of bone marrow derived stem cells (MSCs) on the temporal pathogenesis.1 Conversely, by placing tendons from the same source in culture and thus stress depriving them, we can isolate specific effects on gene expression by added MSCs. The aims of this study were to use in vivo and in vitro data of changes to tendon histopathology and gene expression to define significant factors involved in the development of tensile tendon pathology. Methods: Sheep (n=72) had a hemitransection on the cranial side of their infraspinatus tendon (IT) midway between the bony attachment and the musculotendinous junction. Multipotent heterologous marrow-derived MSCs (30 million in 0.25 ml saline) were injected (with ultrasound guidance) into the transection site 2 (n=18) or 11 (n=18) weeks after surgery. IT were harvested from six animals in each of the resulting four groups (non operated controls (NOC); cut but no MSCs (Cut); Cut & MSCs @ 2 weeks; Cut and MSCs @ 11 weeks), at 13, 26 and 52 weeks post transection. IT were fixed, sectioned and stained with H&E (cellular and vascular pathology), picrosirius red (collagen fibre alignment) and toluidine blue (proteoglycans). Resulting sections were then scored for the above outcomes independently by two observers blinded to treatment. Other portions of tendon were snap-frozen for RNA isolation followed by real time RT-PCR using ovine specific primers for matrix and metalloproteinase genes. Normal or pathological IT explants were also harvested for co-culture for 1 or 5 days with MSCs, before and after freeze/thawing tendon explants to devitalise tendon cells. Gene expression of the MSCs from these co-cultures was measured by RT-PCR and analysed by regression modelling. Results: MSCs injected intralesionally at both time points, significantly ameliorated histopathological changes in stress-deprived tensile tendon 3 months after surgery (p<0.05) but only injections at 11 weeks after surgery were effective in the long-term (52 weeks, p<0.05). While MSCs modulated the gene expression profile compared to Cut, particularly at 3 months, there was little difference between tendons injected 2 and 11 weeks. Tendon extracellular matrix, pathology, the presence of live cells and time cultured, significantly and differentially altered gene expression by MSCs in vitro (figure 1 ), but did not suggest the MSCs were differentiating into tenocytes. Discussion: We have demonstrated that MSC injections can be effective in reducing surgically-induced tendon pathology and that timing of injection is critically important to the long-term benefit. The in vitro changes in MSC expression suggest that both the tenocytes and the condition of the extracellular environment determine the secretome of the injected cells, and that the MSCs are responding to feedback from their immediate environment. MSCs have potential in the development of a cellular therapy to treat tendinopathy that develops after injury.